2020
DOI: 10.1186/s13063-020-04431-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and evaluation of a nurse-led decision-coaching program for healthy breast cancer susceptibility gene (BRCA1/2) mutation carriers: a study protocol for the randomized controlled EDCP-BRCA study

Abstract: Background: Female BRCA mutation carriers have an increased lifetime risk for breast and ovarian cancer compared to the general population. Women who carry this mutation have several options to deal with their cancer risk, such as risk-reducing surgeries or intensified breast cancer screening. Previous research has shown that preferences in this scenario are highly dependent on affected women's personalities and value systems. To support these women in the decision-making process, a structured decision support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
11
0
2
Order By: Relevance
“…The Centers of the German Consortium for Familial Breast and Ovarian Cancer are committed to the principles of non-directive counselling and the shared decision-making concept in standard operating procedures, thereby ensuring an adequate risk communication about the risk of developing disease and the risk reduction by preventive surgeries [25,26]. A detailed description of usual care can be found in the study protocol [27] and will be provided in the scope of the accompanying process evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The Centers of the German Consortium for Familial Breast and Ovarian Cancer are committed to the principles of non-directive counselling and the shared decision-making concept in standard operating procedures, thereby ensuring an adequate risk communication about the risk of developing disease and the risk reduction by preventive surgeries [25,26]. A detailed description of usual care can be found in the study protocol [27] and will be provided in the scope of the accompanying process evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that patients with different personalities have different attitudes towards illness, and that desire to express their values such as patients extrovert personalities are more likely to participate in shared decision-making with healthcare. 88 …”
Section: Discussionmentioning
confidence: 99%
“…To date there is still no DA for BRCA1/2 mutation carriers for German-speaking countries that is used routinely in clinical practice. Various support tools for BRCA1/2 mutation carriers are currently in development or clinical testing, however, including two DAs 23 , 51 , 52 , 53 . In developing a German DA, already existing international DAs can serve formally as a basis and the content regarding treatment recommendations must be adapted to the German guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Aktuell befinden sich jedoch verschiedene Unterstützungsinstrumente für BRCA1/2 -Mutationsträgerinnen in der Entwicklung bzw. klinischen Prüfung, darunter auch 2 EH 23 , 51 , 52 , 53 . Bei der Entwicklung einer deutschen EH können bereits vorhandene internationale EH formal als Grundlage dienen, inhaltlich muss eine Anpassung der angebotenen Handlungsempfehlungen an die deutschen Leitlinien erfolgen.…”
Section: Schlussfolgerungunclassified